A metal-free picolinamide assisted electrochemical ortho-trifluoromethylation of arylamines. (5th January 2021) - Wang, Kai; Hou, Jiahao; Wei, Tingting; Zhang, Changjun; Bai, Renren; Xie, Yuanyuan
Graphical abstract: Highlights: An electrochemical method for the synthesis of ortho -trifluoromethylation of arylamines was developed. The addition of transition metals and oxidants was not required. The desired products were obtained in moderate to good yields. The study of the reaction mechanism revealed that a radical step was involved in this transformation. Abstract: An eco-friendly and effective electrochemical process was developed for the ortho -trifluoromethylation of arylamines using CF3 SO2 Na as the trifluoromethyl source, affording the desired products in moderate to good yields with high regioselectivity under mild reaction conditions. Importantly, the requirement for both transition metals and oxidants utilized in previous methods were avoided. A radical mechanism was proposed on the basis of various control experiments.